2020
DOI: 10.1186/s12944-020-01356-x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of CYP24A1 variants in coronary heart disease among the Chinese population

Abstract: Background: Cytochrome P450 (CYPs) participate in the mechanisms of cardiovascular disease. The purpose of this research was to evaluate the contributions of CYP24A1 variants to coronary heart disease (CHD) among the Chinese Han population. Methods: This study included 505 CHD cases and 508 controls. Four variants of CYP24A1 (rs2762934, rs1570669, rs6068816 and rs2296241) were chosen and genotyped by the Agena MassARRAY system among the Chinese population. The linkage between CYP24A1 variants and CHD risk were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In addition to the classic risk factors such as age, smoking, drinking, hypertension, diabetes, and hypercholesterolemia [ 9 ], a large number of studies have confirmed that genetic factors play an important role in the occurrence and development of CHD [ 10 ]. Besides, many genetic variants such as LPA [ 11 ], CYP24A1 [ 12 ], CYP2C19 [ 13 ], PNPLA3 I148M [ 14 ], and IL-7 / 7R [ 15 ] can significantly affect the susceptibility of CHD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the classic risk factors such as age, smoking, drinking, hypertension, diabetes, and hypercholesterolemia [ 9 ], a large number of studies have confirmed that genetic factors play an important role in the occurrence and development of CHD [ 10 ]. Besides, many genetic variants such as LPA [ 11 ], CYP24A1 [ 12 ], CYP2C19 [ 13 ], PNPLA3 I148M [ 14 ], and IL-7 / 7R [ 15 ] can significantly affect the susceptibility of CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Although no studies have shown a relationship between the polymorphisms of CYP24A1, CYP27B1, and NAFLD, these variants have been extensively investigated in other diseases, such as organ-specific autoimmune endocrine diseases (Ma et al, 2020), CVD (Qian et al, 2020), metabolic diseases (Yu et al, 2020), and multiple cancers (Hibler et al, 2015;Torkko et al, 2020). Our results also confirmed that NAFLD patients with a combined load of unfavorable alleles (rs2296241-A, rs2248359-T, and rs4646536-T) exhibited an association with the increase in NAFLD risk, and this association was also in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 1,25(OH) 2 D 3 can be decomposed by 1,25-hydroxyvitamin-D3-24-hydroxylase encoded by cytochrome P450 family 24 subfamily A member 1 (CYP24A1) gene, maintaining the balance of vitamin D metabolism in vivo. Several genetic studies have reported that common single nucleotide polymorphisms (SNPs) in vitamin D pathway genes are associated with low-level serum 25(OH)D, including vitamin D receptor (VDR), vitamin D-binding protein (VDBP), CYP2R1, CYP24A1, and CYP27B1 (Bedogni et al, 2006;Angulo et al, 2007;Wang et al, 2010;Boyle et al, 2012;Visscher et al, 2012;Zhu and DeLuca, 2012;Dastani et al, 2013;Braithwaite et al, 2015;Hibler et al, 2015;Woods et al, 2015;Jolliffe et al, 2016;Jung and Shin, 2016;Cheng et al, 2017;Thacher and Levine, 2017;Gibson et al, 2018; National Workshop on Fatty Liver and Alcoholic Liver Disease, Chinese Society of Hepatology, Association et al, 2018;Arai et al, 2019;Cho et al, 2019;Younossi, 2019;Zhang et al, 2019;Liu et al, 2020;Ma et al, 2020;Qian et al, 2020;Torkko et al, 2020;Yu et al, 2020). Genome-wide association studies (GWAS) have also identified that variants near these genes are associated with vitamin D status (Wang et al, 2010;Visscher et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide studies have emphasized the role of vitamin D pathway genes in many processes that are strongly linked to NAFLD, such as immunological alteration, cellular differentiation, and inflammatory processes [133,134]. Various genetic studies have revealed frequent single nucleotide polymorphisms (SNPs) in vitamin D pathway genes and highlighted their association with low serum vitamin D levels both in healthy subjects and those with hepatitis, such as the genes for CYP2R1 and CYP27B1 [133], while mutations in the CYP24A1 gene, responsible to vitamin D degradation [135], causes calcitriol elevation [136]. A case-control study that investigated the effect of vitamin D gene SNPs has shown that alleles CYP24A1 rs2296241-A, rs2248359-T, and CYP27B1 rs4646536-T were all considered a risk factor for NAFLD when combined with other clinical factors [134].…”
Section: The Association Between Nafld and Vddmentioning
confidence: 99%